EP364 Prognostic value of ddPCR HPV in lymph nodes of early cervical cancer. (1st November 2019) - Montero Macías, R; Veyer, D; Mandavit, M; Wack, M; Rance, B; Bonsang-Kitzis, H; Deloménie, M; Bats, A-S; Ngo, C; Balaya, V; Koual, M; Nguyen-Xuan, H-T; et al.
Abstract : Introduction/Background: In early stages (Ia to IIa1) of cervical cancer (CC), nodal status is the cornerstone of treatment algorithm and patients with nodal metastasis (N+) present worse survival. However, 10–15% of patients without nodal metastasis (N0) present the same survival to patients N+. No clinical, imaging or pathological risk-factor is today effective to select these patients for different management. In HPV-related cancers, like CC, HPV DNA could be assimilated to tumoral DNA and represent an interesting marker of node metastasis. In this study, we evaluate the presence of tumoral HPV DNA in pelvic lymph nodes (PLN) by new ultrasensitive droplet-based digital polymerase chain reaction (ddPCR) to explore it as a new additional biomarker to classify early stages of CC. Methodology: This study was conducted on 30 patients from Senticol prospective trials. Formalin-fixed paraffin (FFPE) embedded tumours and associated pelvic lymph nodes samples were available for only 25 patients in our institution. In HPV16-positive tumour patients (n=18; 3 patients were N+ and 15 N0), we performed the specific HPV16 ddPCR in associated pelvic lymph node samples after a manual DNA extraction. Simultaneously, albumin was detected as internal control. Results: Unfortunately, 22.2% of PLN were not interpretable (NI) with a very low level of albumin suggesting that no sufficient amount of DNA was extracted for HPV16 tumoral DNA interpretation. It could be explained by DNA destruction over time considering that FFPE biopsies were collected from 2005 to 2011. Insufficient follow-up data is <6 months (2 patients). Conclusion: As expected, HPV16 tumoral DNA was detected in N+ patient PLN. In the N0 group, 40% (2/5) of patients with HPV16-positive PLN have relapsed regarding 12, 5% (1/8) relapsing patients in the group of HPV16-negative PLN. These interesting preliminary results invite to test this new molecular biomarker in largest cohorts to evaluate its interest in early CC management. Disclosure: Nothing to disclose.